2023
DOI: 10.4028/p-g6ca92
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of NaF on the Photoluminence Properties of Sammarium Ion Doped on Fluoro-Borophosphate Glass Medium

Abstract: Fluoro-borophosphate glass containing Natrium Fluoride (NaF) doped with Samarium ion 1 mol% concentration. The glass compositions based on 49P2O5-5B2O3-15ZnO-15Li2O-15NaF-1Sm2O3 are prepared by melting and quenched technique. The optical and photoluminescence were obtained from the UV-Vis-NIR spectrophotometer and spectrofluorophotometer. The ground state 6H5/2 as the start transition in the absorption spectrum and the Judd-Ofelt intensity parameters (2, 4, and 6) were determined. The emission spectra of borop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Radiative properties of Erbium doped Lithium Fluorophosphate glasses.Quantum efficiency in Table5show that Er2 glass also has the highest value. Based on these results, it can be concluded that EDLF glasses is superior for use in the development of NIR optical amplifier devices [16][17][18][19][20]…”
mentioning
confidence: 88%
“…Radiative properties of Erbium doped Lithium Fluorophosphate glasses.Quantum efficiency in Table5show that Er2 glass also has the highest value. Based on these results, it can be concluded that EDLF glasses is superior for use in the development of NIR optical amplifier devices [16][17][18][19][20]…”
mentioning
confidence: 88%